Histocompatibility evaluation of combination of gypsum with carbonated hydroxyapatite as bone substitutes in subcutaneous tissue - Ika Dewi Ana, Dyah Listyarifah Rina Susilowati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2011)
Combination of gypsum with carbonated hydroxyapatite (CHA) has shown to improve bone healing process. Softtissue biocompatibility test is required prior to clinical application of bone substitutes since the materials contactwith the soft tissues upon application and can cause severe inflammatory response. The aim of this study was toevaluate histocompatibility of gypsum compared to combination of gypsum-CHA in subcutaneous tissue. Disks ofgypsum and gypsum-CHA were implanted on paravertebral subcutaneous tissue of 25 male Wistar rats. Histologicalsection were stained with Hematoxylin Eosin then evaluated and scored with a histological grading scale for softtissueimplants. A two-way ANOVA was used to analyze the histomorphometrical results with 95% confidenceinterval (p<0.05). The results showed that acute inflammatory cells were found in both groups at 6 hour and on day5 and 7 after implantation at similar level. Chronic inflammatory cells and capsule were observed on day 7, 14, and21. Moreover, there was no significant difference (p>0.05) of histomorphometrics score between both implants ineach implantation periods. It could be concluded that histocompatibility level of gypsum and combination of gypsum-CHA to soft tissue was the same until day 21 iof mplantation.Key words: gypsum - carbonated hydroxyapatite â biocompatibility â histocompatibility - subcutaneous implant